A novel active braze composition design route for C/C composite using Fe as active element. (30th August 2021) - Zhang, Guifeng; Zhang, Yu; Bao, Jiandong; Yang, Guanjun
Abstract: A novel active braze composition design route for carbon fiber reinforced carbon composite (C/C) using weak carbide former of Fe as active element based on Fe-C eutectic reaction was firstly proposed and demonstrated to increase service temperature of brazed C/C joint. Five kinds of commercial Fe-based sheets, including commercially pure iron (CPFe), mild steel, Invar alloy (4J36), stainless steels (SS) 304 and 630, were used as braze to investigate wettability. Brazing was performed by rapid induction heating in flowing argon at 1250 °C for 5 min under 0.5 MPa. C/C composite and each braze were dissolved well by Fe-C eutectic reaction, forming (i) intimate interface without gap defect, and (ii) dense bond seam consisting of retained austenite with high carbon content (∼35 at.%) without (only for SS) or with pro-eutectic carbides. CPFe showed the maximum penetration depth in C/C composite up to 25 μm, while 630SS exhibited the smallest contact angle (20–45°) and detectable interfacial carbide, resulting in a shear strength of 16 ± 1 MPa. The results demonstrated that Fe is a promising active element for C/C composite with cheap, rapid, robust, and high remelting temperature attractive features. Graphical abstract: Image 1